KAMPANYE PENERAPAN 3M MASA PANDEMI COVID-19 SEBAGAI UPAYA MEMUTUS RANTAI PENYEBARAN VIRUS CORONA - Siregar, Ballian; Yulistiani, Indriati (Universitas Esa Unggul, 2021)
Severe acute respiratory syndrome coronavirus 2 (SARS-Cov-2), better known as the Corona Virus, has changed the social order. In order to break the chain of spread of the corona virus, the Government ha called all elements of society to discipline health promotion by adhering to the 3M concept; wear a mask, washing hands and keep the distance. The government's invitation was carried out in concrete steps by the lecturers and students of the Faculty of Communication Sciences at Esa Unggul University in the form of implementing 3M campaign toward members of the Oemah Daon Education and Social Foundation in Daon Lembur Village, Rajeg District, Tangerang Regency. The aim of the Campaign is that Foundation members are disciplined in maintaining health even though they have to do activities outside the home. The campaign used a zoom meeting for 135 minutes which was attended by 82 participants, they are from the Foundation, students of SMK 9 Tangerang Regency by presenting competent speakers. It is hoped that this campaign will encourage community discipline to comply with the 3M program.Â Keywords: covid-19, campaign 3M, SARS-Cov-2